Alternatives in Counterfactuals: What Is Right and What Is Not. (21st March 2022) - Romoli, Jacopo; Santorio, Paolo; Wittenberg, Eva
Abstract: Classical semantics for counterfactuals is based on a notion of minimal change: If A, would C says that the worlds that make A true and that are otherwise minimally different from the actual world are C -worlds. This semantics suffers from a well-known difficulty with disjunctive antecedents (see e.g. Alonso-Ovalle, 2009 ; Willer, 2018 ; Santorio, 2018, a.o.). In a recent study, Ciardelli, Zhang, and Champollion (Ciardelli et al., 2018b ; henceforth, CZC) present new, related difficulties for the classical approach having to do with unpredicted differences between counterfactuals with De Morgan-equivalent antecedents, and related pattern of inferences. They propose a new semantics for counterfactuals, which builds on inquisitive semantics (see Ciardelli et al., 2018a ) and gives up on minimal change. Building on this debate, we report on a series of experiments that investigate the role of overt negation in this data. Our results replicate CZC's main effects, but they also indicate that those effects are linked to the presence of overt negation. We propose a novel account, based on three key assumptions: (i) the semantics for counterfactuals does involve a notion of minimal change, after all; (ii) the meanings of disjunction and negation are associated with alternatives, which interact with the meaning of counterfactuals; (iii) the alternatives generated by negation are partially determined by the question under discussion (QUD). We compare our account with other existing accounts, including CZC's own proposal, as well as Schulz (2019) and Bar-Lev & Fox (2020) ones.